Estimation of 2D distributions of electron density and temperature in the JET divertor from tomographic reconstructions of deuterium Balmer line emission. (December 2020) - Karhunen, J.; Lomanowski, B.; Solokha, V.; Aleiferis, S.; Carvalho, P.; Groth, M.; Kumpulainen, H.; Lawson, K.D.; Meigs, A.G.; Shaw, A.; ,
Highlights: 2D ne and Te estimates obtained from deuterium Balmer line ratios in JET divertor. High ne observed to shift from strike point to above X-point in L-mode detachment. Divertor Te observed to fall from 3—4 eV to 0.5—1.0 eV in L-mode detachment. 2D estimates within 25% agreement with other spectroscopic ne and Te measurements. Abstract: Estimates for 2D distributions of electron density, ne, and temperature, Te, have been obtained using reflection-corrected tomographic reconstructions of deuterium Balmer line emission in the JET divertor. The solutions are obtained by a two-dimensional Monte Carlo optimization model, based on intensity ratios of the Balmer Dα, Dγ and Dε emission and the ADAS photon emission coefficients with additional constraints provided by line-integrated spectroscopic measurements of ne and Te . Synthetic benchmarks utilizing EDGE2D-EIRENE simulation outputs yield reproduction of reference ne and Te distributions within 25% with statistical error estimates of 5–15%. Experimental analysis of an L-mode ne ramp shows extension and movement of the outer divertor high-ne region with ne, div up to 1.5 × 10 20 m −3 from the outer strike point to above the X-point and decrease of the divertor Te to the range of 0.5–1.0 eV within 25% agreement with the line-integrated measurements. Comparison between the local estimates and their corresponding line integrals suggests underestimation of ne and Te by up to 75% and 50%, respectively, due to the geometric effects of line integration.